The oldest described eurypterid: a giant Middle Ordovician (Darriwilian) megalograptid from the Winneshiek Lagerstätte of Iowa - Lamsdell, James C. (BMC Evol Biol, 2015)
BACKGROUND: Eurypterids are a diverse group of chelicerates known from ~250 species with a sparse Ordovician record currently comprising 11 species; the oldest fully documented example is from the Sandbian of Avalonia. The Middle Ordovician (Darriwilian) fauna of the Winneshiek Lagerstätte includes a new eurypterid species represented by more than 150 specimens, including some juveniles, preserved as carbonaceous cuticular remains. This taxon represents the oldest described eurypterid, extending the documented range of the group back some 9 million years. RESULTS: The new eurypterid species is described as Pentecopterus decorahensis gen. et sp. nov.. Phylogenetic analysis places Pentecopterus at the base of the Megalograptidae, united with the two genera previously assigned to this family by the shared possession of two or more pairs of spines per podomere on prosomal appendage IV, a reduction of all spines except the pair on the penultimate podomere of appendage V, and an ornamentation of guttalate scales, including angular scales along the posterior margin of the dorsal tergites and in longitudinal rows along the tergites. The morphology of Pentecopterus reveals that the Megalograptidae are representatives of the derived carcinosomatoid clade and not basal eurypterids as previously interpreted. CONCLUSIONS: The relatively derived position of megalograptids within the eurypterids indicates that most eurypterid clades were present by the Middle Ordovician. Eurypterids either underwent an explosive radiation soon after their origination, or earlier representatives, perhaps Cambrian in age, remain to be discovered. The available instars of Pentecopterus decorahensis suggest that eurypterids underwent extreme appendage differentiation during development, a potentially unique condition among chelicerates. The high degree of appendage specialization in eurypterids is only matched by arachnids within chelicerates, supporting a sister taxon relationship between them. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12862-015-0443-9) contains supplementary material, which is available to authorized users.